Physical Activity and Sedentary Behavior in Breast and Colon Cancer Survivors Relative to Adults Without Cancer - Shi, J.; MacInnis, R.; Boyle, Terry; Vallance, J.; Winkler, E.; Lynch, B. (Elsevier Inc., 2017)
Objective To assess differences in accelerometer-assessed moderate- to vigorous-intensity physical activity (MVPA), light-intensity physical activity, and sedentary time between cancer survivors and adults without cancer. Patients and Methods Accelerometer data collected from 241 breast cancer survivors (ACCEL-Breast study, 2013) and 171 colon cancer survivors (ACCEL-Colon study, 2012-2013) were pooled with data collected from adults without cancer (Australian Diabetes, Obesity and Lifestyle accelerometer substudy, 2011-2012). Linear regression was used to estimate differences in physical activity and sedentary behavior levels between cancer survivors and adults without cancer, adjusted for potential confounding factors. Results The mean MVPA was significantly higher among breast cancer survivors than among females who had not had cancer (29 vs 22 min/d; P<.001). Colon cancer survivors had significantly lower levels of light activity than did adults without cancer (311 vs 338 min/d; P<.001), more sedentary time (532 vs 507 min/d; P=.003), and more prolonged sedentary time (210 vs 184 min/d; P=.002). Conclusion Contrary to findings from previous research (based on self-reported physical activity), cancer survivors engaged in more (breast) or equivalent (colon) MVPA compared with adults without cancer. Differences between colon cancer survivors and adults without cancer for light activity and sedentary behavior highlight the importance of considering the full activity spectrum in the context of cancer control.